The Clan and the Corporation: Sustaining Cooperation in China and Europe - Avner Greif; Guido Tabellini (Center for Economic Studies and ifo Institute (CESifo), 2015)
Over the last millennium, the clan and the corporation have been the loci of cooperation in China and Europe respectively. This paper examines - analytically and historically - the cultural and institutional co-evolution that led to this bifurcation. We highlight that groups with which individuals identify are basic units of cooperation. Such loyalty groups influence institutional development because intra-group moral commitment reduces enforcement cost implying a comparative advantage in pursuing collective actions. Loyalty groups perpetuate due to positive feedbacks between morality, institutions, and the implied pattern of cooperation.
Keywords: N00; A10; 330